PENGARUH PENERAPAN METODE PEMBELAJARAN BRAIN BASED LEARNING BERBANTUAN BRAIN GYM TERHADAP HASIL BELAJAR PESERTA DIDIK - Ivah S. Fajriati; Safei Safei; Saprin Saprin (Jurnal Biotek, 2017)
This research discusses about learning methods Brain Based Learning (BBL) in the learning outcomes in the matter Coordination System in Class XI IPA MAN 3 Makassar. Purpose of research to the study of students in the subjects of biology using the Brain Based Learning assisted Brain Gym in the class XI MAN 3 Makassar, to determine learning outcomes Learners on the subjects of biology without using Brain Based Learning assisted Brain Gym in the class XI MAN 3 Makassar, and to determine whether there is an influence on the learning outcomes of students in the subjects of biology by using learning methods Brain Based learning (BBL) assisted Brain Gym in the class XI MAN 3 Makassar. The study population was all students of grade XI MAN 3 Makassar. The research sample is class XI IPA 1 (experiment I) and class XI IPA 5 (experiment II) each class of 20 students. The results of study revealed Brain Based Learning teaching methods that are in the very good category indicated by the average value of 83.6. The results of the analysis of hypothesis testing using t-test diperoles thit value = 10.25 and the value ttab = 2.09 with dk 38. Where the value of thit> ttab so H¬0 rejected, Ha is received, thus there are significant learning outcomes of students who are taught through learning methods Brain Based learning (BBL) aided Brain Gym on the material coordination system at grade XI MAN 3 Makassar.